The reasons behind the non-application of the activity based costing system in the service industry in Lebanon. (c2015) - Dandach, Ghiwa Ali (2015)
The Activity Based Costing (ABC) system, despite its spread in the First World Countries and the recognition of its importance also in the third world countries, is not adopted in the service industry in Lebanon while costing output. This thesis seeks the reasons behind the reluctance of decision makers from applying the Activity Based Costing system. The study relied on prior research and studies undertaken on this topic abroad. Hypotheses were developed stating the most significant reasons that were tested through survey and interviews. Eventually, statistical results revealed that the real factors prohibiting the application of the ABC system are the lack of commitment of controllers and employees, the necessity to change internal culture, the availability of financial and time resources and the satisfaction of the current costing system. Other factors sum up as the priority of company to other considerations, and the lack of technology.